Kompetensi SDM dan Kinerja Karyawan: Mediasi Kesenjangan Kompetensi di Keraton Jimbaran Beach Resort - Ni Putu Widiastuti; Mutria Farhaeni; Putu Suweca Nata Udayana (Jurnal Nasional Manajemen Pemasaran dan SDM, 2026)
This study aims to analyze the effect of HR Competence on Employee Performance with Competency Gap as a mediating variable at Keraton Jimbaran Beach Resort. The dynamic nature of the hospitality industry demands a match between employee capabilities and four star service standards. The research method used is quantitative, with questionnaires distributed to the employees of Keraton Jimbaran Beach Resort. Data analysis utilized Partial Least Squares (PLS) to test the relationships between variables. The results show that: (1) HR Competence has a positive and significant effect on Employee Performance; (2) HR Competence has a negative and significant effect on Competency Gap; (3) Competency Gap has a negative and significant effect on Employee Performance; (4) Competency Gap significantly mediates the influence of HR Competence on Employee Performance. These findings imply that the management of Keraton Jimbaran Beach Resort needs to focus on reducing employee capability gaps through targeted training programs to achieve optimal organizational performance